Deep-skin third-harmonic generation (THG) imaging in vivo excited at the 2200 nm window - Xinlin Chen; Yi Pan; Ping Qiu; Ke Wang (Journal of Innovative Optical Health Sciences, 2023)
The skin is heterogeneous and exerts strong scattering and aberration onto excitation light in multiphoton microscopy (MPM). Shifting to longer excitation wavelengths may help reduce skin scattering and aberration, potentially enabling larger imaging depths. However, previous demonstrations of skin MPM employ excitation wavelengths only up to the 1700[Formula: see text]nm window, leaving an open question as to whether longer excitation wavelengths are suitable for deep-skin MPM. Here, in order to explore the longer-wavelength territory, first, we demonstrate characterization of the broadband transmittance of excised mouse skin, revealing a high transmittance window at 2200[Formula: see text]nm. Then, we demonstrate third-harmonic generation (THG) imaging in mouse skin in vivo excited at this window. With 9[Formula: see text]mW optical power on the skin surface operating at 1[Formula: see text]MHz repetition rate, we can get THG signals of 250[Formula: see text][Formula: see text]m below the skin surface. Comparative THG imaging excited at the 1700[Formula: see text]nm window shows that as imaging depth increases, THG signals decay even faster than those excited at 2200[Formula: see text]nm. Our results thus uncover the 2200[Formula: see text]nm window as a new, promising excitation window potential for deep-skin MPM.